Evaluation of the effects of food on levodropropizine controlled-release tablet and its pharmacokinetic profile in comparison to that of immediate-release tablet - Lee, Soyoung; Nam, Kyu Yeol; Oh, Jaeseong; Lee, Seung Hwan; Cho, Sang Min; Choi, Youn Woong; Cho, Joo Youn; Lee, Beom Jin; Hong, Jang Hee (Drug Design, Development and Therapy, 2018)
Background: Levodropropizine is a non-opioid antitussive agent that inhibits cough reflex by reducing the release of sensory peptide in the peripheral region. To improve patients’ compliance, a controlled-release (CR) tablet is under development. The aim of this study was to compare the pharmacokinetic (PK) profiles of the CR and immediate-release (IR) tablets of levodropropizine. In addition, the effect of food on the PK properties of levodropropizine CR tablet in healthy subjects was evaluated. Subjects and methods: A randomized, open-label, multiple-dose, three-treatment, three-period, six-sequence, crossover study was conducted on 47 healthy subjects. All subjects were randomly assigned to one of the six sequences, which involve combinations of the following three treatments: levodropropizine IR 60 mg three times in the fasted state (R), levodropropizine CR 90 mg two times in the fasted state (T), and levodropropizine CR 90 mg two times in the fed state (TF). Serial blood samples were collected up to 24 h after the first dose. Tolerability was assessed based on the vital signs, adverse events (AEs), and clinical laboratory tests. Results: Levodropropizine CR showed lower maximum drug concentration (Cmax) and similar total exposure compared to levodropropizine IR. The geometric mean ratios (GMRs) (90% confidence intervals [CIs]) of T to R for the Cmax and area under the concentration–time curve from the 0 to 24 h time points (AUC0–24h) were 0.80 (0.75–0.85) and 0.89 (0.86–0.93), respectively. In the fed group, levodropropizine CR showed exposure similar to that in the fasted group. The GMRs (90% CIs) of TF to T for the Cmax and AUC0–24h were 0.90 (0.85–0.97) and 1.10 (1.05–1.14), respectively. No serious AEs occurred with both levodropropizine CR and IR tablets. Conclusion: Total systemic exposure for levodropropizine was similar in subjects receiving the CR and IR formulations in terms of the AUC. Although food delayed the absorption of levodropropizine CR, systemic exposure was not affected.
Keywords: Administration, Oral; Adult; Cross-Over Studies; Drug Tolerance; Humans; Male; Middle Aged; Propylene Glycols; Tablets; Young Adult; Controlled-release; Food effect; Immediate-release; Pharmacokinetics